Visibility Graphs of Anchor Polygons - Boomari, Hossein; Zarei, Alireza (Journal of Graph Algorithms and Applications, 2022)
The visibility graph of a polygon corresponds to its internal diagonals and boundary edges. For each vertex on the boundary of the polygon, we have a vertex in this graph and if two vertices of the polygon see each other there is an edge between their corresponding vertices in the graph. Two vertices of a polygon see each other if and only if their connecting line segment completely lies inside the polygon. Recognizing visibility graphs is the problem of deciding whether there is a simple polygon whose visibility graph is isomorphic to a given graph. Another important problem is to reconstruct such a polygon if there is any. These problems are well known and well-studied, but yet open problems in geometric graphs and computational geometry. However, they have been solved efficiently for special cases where the target polygon is known to be a tower or a spiral polygon. In this paper, we propose a linear time algorithm to solve these recognizing and reconstruction problems for another type of polygons, named anchor polygons.